Multiple gradient structures driving higher tensile strength and good capacity to absorbed energy in aluminum wire processed by cryogenic pre-torsion. (15th March 2022) - Cai, S.L.; Li, D.Q.; Liu, S.C.; Cheng, Y.F.; Li, J.H.; Koch, C.C.
Abstract: Aluminum wire with multiple gradient structures (MGSs) was processed by cryogenic pre-torsion. Microstructural characterizations illustrate that grain size gradient, dislocation density gradient, precipitate size gradient, and precipitate volume fraction gradient were produced during the cryogenic pre-torsion process of aluminum wire. Uniaxial tensile tests reveal that the multiple gradient structured aluminum wire possesses higher strength without compromising the capacity to absorbed energy. A theoretical model considering these MGSs was proposed to explain the excellent mechanical properties. The theoretical analyses reveal that the high strength is attributed to the fine grains, high dislocation density, and large volume fraction of precipitate. The gradient yield stress resulting from MGSs promotes the accumulation of geometrically necessary dislocations (GNDs). This provides extra strain hardening capability for improving the capacity to absorbed energy. Graphical abstract: Image, graphical abstract